Mini-invasive anterior approach in total hip arthroplasty: short-term follow-up - Paraskevopoulos, A.; Marenghi, P.; Alesci, M.; Pogliacomi, F. (Acta Biomedica Atenei Parmensis, 2014)
Purpose: To evaluate short-term follow-up of patients treated with total hip arthroplasty through minimally invasive anterior approach. Methods: Twenty-four patients, surgically treated with this approach from January 2010 to December 2010. We measured the blood loss, the number of transfusions, the time of surgery, the length of hospital stay and intra and postoperative complications. All patients were clinically evaluated by Womac and Harris Hip Score 12 months after surgery. Radiographic views were performed postoperatively and at 1, 3 and 12 months after surgery in order to evaluate component positioning. Results: The mean value of total blood loss was 1050 ml, the number of transfusions after surgery was on average 0.85. The mean time of surgery was 111 minutes. The mean hospital stay was 6.5 days. The radiographic views showed a correct component placement. We didn’t encounter any complication and the mean score of Womac and Harris Hip Score was satisfactory in all cases. Conclusions: Minimally invasive anterior approach provides good short-term results. However, long-term studies are needed to confirm this evaluation. (www.actabiomedica.it)